Estimation of genetic parameters for milking temperament in Holstein-Gyr cows - Batista Taborda, Paula A.; Valente, Tiago da Silva; de Lima Carvalhal, Monique Valéria; da Silva, Marcos Vinicius Gualberto Barbosa; Paranhos da Costa, Mateus J. R. (Frontiers in Animal Science, 2023)
Dairy cattle with poor temperament can cause several inconveniences during milking, leading to labor difficulties, increasing the risk of accidents with animals and workers, and compromising milk yield and quality. This study aimed to estimate variance components and genetic parameters for milking temperament and its genetic correlations with milk yield in crossbred Holstein-Gyr cattle. Data was collected in three commercial farms, resulting in 5,904 records from 1,212 primiparous and multiparous lactating cows. Milking temperament (MT) measured as the milking temperament of each cow, was assessed during pre-milking preparation(RP) and when fitting of the milking cluster(RF) by ascribing scores from 1 (cow quietly) to 8 (cow very agitated). The number of steps and kicks were also recorded during pre-milking preparation (SRP and KRP, respectively) and when fitting of the milking cluster (SRF and KRF, respectively). Milk yield (MY) was obtained from each farm database. Genetic parameters were estimated using the THRGibbs1f90 program applying a threshold model, which included 89 contemporary groups as fixed effect, animal age at the assessment day and the number of days in milking as covariates, and direct additive genetic and residual effects as random effects. Heritability estimates were MT=0.14±0.03 (for MRP and MRF), MY=0.11±0.08, SRP=0.05±0.03, KRP=0.14±0.05, SRF=0.10±0.05 and KRF=0.32±0.16. Repeatability estimates were 0.38±0.05; 0.42±0.02; 0.84±0.006 for MTRP, MTRF and MY, respectively; 0.38±0.02, 0.30±0.07, 0.52±0.02, 0.46±0.15 for SRP, KRP, SRF, and KRF, respectively. The estimates of most genetic correlation coefficients between MTRP-MTRF were all strong and positive (MTRR-MTRF=0.63±0.10, MTRP-SRP=0.65±0.12, MTRP-KRP=0.56±0.16, MTRF-SRF=0.77±0.06, MTRF-KRF=0.56±0.34), except for MY (MTRP-MY=0.26±0.26 and MTRF-MY=0.21±0.23). Despite the low magnitude of MT heritability, it can be included as a selection trait in the breeding program of Holsteins-Gyr cattle. Due to the low accuracy of the genetic correlation estimates between MT and MY and the high range of the 95% posterior density interval, it cannot be affirmed by this study that the selection on a milking temperament trait will infer on milk yield. More data is therefore needed per cow and more cows need to be observed and measured to increase the reliability of the estimation of these correlations to be able to accurately interpret the results.